Non-contact Study of Surfaces Created Using the AWJ Technology - Krenický, Tibor (Manufacturing Technology Journal, 2015)
Spatial measurement and evaluation of the surface profile parameters provide valuable and useful information about the relationship between the geometric characteristics of the surface and its functional properties. Evaluating the structure of surface area may help to explain a variety of problems in manufacturing technologies as it allows detailed quantitative study of geometric and dimensional changes of the surface profiles. AWJ cutting still generates unrevealed questions regarding interactions of the cutting material with the work-piece. The article presents experimental study of surface of steel material after AWJ cutting with usage of optical method that was selected as universal method that overcomes some of the shortcomings of contact methods.
Keywords: abrasive water-jet cutting; profile parameters; roughness; non-contact measurement; striation